ANALISIS SALURAN DISTRIBUSI PUPUK BERSUBSIDI UREA (PUSRI) DI KECAMATAN BELITANG KABUPATEN OKU TIMUR - Imam Sulaiman (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The objectives of this research are: (1) To know the distribution channel of urea subsidized fertilizer (PUSRI) at MT I in Belitang Sub-district of OKU Timur Regency, (2) To calculate and to know fertilizer requirement and subsidized fertilizer allocation of urea (PUSRI) ) Which is absorbed in Belitang District of East OKU Regency. This research was conducted from February to April of 2014 on the distribution of urea subsidized fertilizer (PUSRI) in Belitang Sub-district of East OKU Regency with survey method. The research found that the distribution of urea subsidized fertilizer (PUSRI) in Belitang Sub-district was done indirectly through authorized retailers Which has been determined by the next distribution of GAPOKTAN or KUD filed RDKK according to the needs of each farmer group. After that each member of each new farmer group can take part of the fertilizer based on the RDKK as well as with the agreed upon system starting from the price of the amount and the payment system whether it will be paid in cash or seasonally (after the pen). The amount of urea subsidized fertilizer (PUSRI) absorbed from 9 villages in Belitang sub-district is ± 436,800 tons / LG / MT I with average of each village absorbing urea subsidized fertilizer (± PUSRI) of ± 43,680 tons / LG / MT I or about 90%. Meanwhile, the number of urea subsidized fertilizers (PUSRI) not absorbed from 9 villages in Belitang sub-district is ± 45.100 tons / LG / MT I with average of each urea subsidized fertilizer village (PUSRI) not absorbed as much as ± 4,510 tons / LG / MT I or about 10%. Thus, urea subsidized fertilizers (PUSRI) from 9 villages in Belitang sub-district are absorbed, rather than unabsorbed.